دور أساليب التسويق المباشر في دعم الميزة التنافسية: دراسة تطبيقية على عملاء شركة مصر للطيران للأسواق الحرة - حامد، أحمد سعيد Hamed, Ahmed Said; الحيوان، حسن عبدالمنعم Alhayawan, Hasan Abdulmoneim (جامعة عين شمس - كلية التجارة, 2019)
Direct marketing is part of the marketing communication mix that has emerged to replace traditional promotional tools, in order to reach a specific mechanism that directs communications efforts and ensures that they are not contradictory in content and form. Today, with the large and growing developments in the world of technology and communications, and the great competition between companies to maintain existing customers and acquire new customers, the companies went directly to customers and consumers in their places to identify their needs and work to satisfy them The business environment within duty free is facing stiff competition due to the radical changes and rapid procedures taking place in its surroundings and the entry of strong competitors from 2004, in this way, Egypt Air duty free has become to adapt to its environment to ensure its survival, relying on mechanisms and factors that strengthen its competitiveness to gain competitive advantages that distinguish it from its competitors. Otherwise, competition risks extend their presence and affect their position within the market
Keywords: إدارة التسويق -- الميزة التنافسية -- الأسواق الحرة -- سلوك المستهلك -- شركات الطيران -- مصر